Chip-less wireless electronic skins by remote epitaxial freestanding compound semiconductors - Kim, Yeongin; Suh, Jun Min; Shin, Jiho; Liu, Yunpeng; Yeon, Hanwool; Qiao, Kuan; Kum, Hyun S; Kim, Chansoo; Lee, Han Eol; Choi, Chanyeol; Kim, Hyunseok; Lee, Doyoon; et al. (Science (American Association for the Advancement of Science), 2022)
Recent advances in flexible and stretchable electronics have led to a surge of electronic skin (e-skin)-based health monitoring platforms. Conventional wireless e-skins rely on rigid integrated circuit chips that compromise the overall flexibility and consume considerable power. Chip-less wireless e-skins based on inductor-capacitor resonators are limited to mechanical sensors with low sensitivities. We report a chip-less wireless e-skin based on surface acoustic wave sensors made of freestanding ultrathin single-crystalline piezoelectric gallium nitride membranes. Surface acoustic wave-based e-skin offers highly sensitive, low-power, and long-term sensing of strain, ultraviolet light, and ion concentrations in sweat. We demonstrate weeklong monitoring of pulse. These results present routes to inexpensive and versatile low-power, high-sensitivity platforms for wireless health monitoring devices.